Poultry production in hot climates [ - Daghir, N. J. [ (Nuhad Joseph)] , 1935- (CABI, 2008)
Describes how the detrimental effects of heat stress can be reduced through the manipulation of housing, breeding, and nutrition and management. This book contains contributions on controlled-environment housing, waterfowl, and breeding fast-growing brolers.